2017
DOI: 10.1177/2325967117729147
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Parental Influence on Youth Athlete Specialization: A Survey of Athletes’ Parents

Abstract: Background:Youth athlete specialization has been linked to decreased enjoyment, burnout, and increased injury risk, although the impact of specialization on athletic success is unknown. The extent to which parents exert extrinsic influence on this phenomenon remains unclear.Purpose/Hypothesis:The goal of this study was to assess parental influences placed on young athletes to specialize. It was hypothesized that parents generate both direct and indirect pressures on specialized athletes.Study Design:Cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
(37 reference statements)
2
31
0
Order By: Relevance
“…These results are consistent with previous research in a larger sample of 1000 parents of adolescent athletes from various sports, which reported that only 43% of parents believed that specialization increased the chances of overuse injury [9]. Previously, sport specialization has been repeatedly identified as a risk factor for injury in various sports [4][5][6]16], although evidence for an association between specialization in baseball and overuse injury is mixed [17]. Our results indicate that many parents may not be aware of the research linking specialization with an increased risk of injury, or perhaps more likely, view the potential benefits of specialization as outweighing the potential injury consequences.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous research in a larger sample of 1000 parents of adolescent athletes from various sports, which reported that only 43% of parents believed that specialization increased the chances of overuse injury [9]. Previously, sport specialization has been repeatedly identified as a risk factor for injury in various sports [4][5][6]16], although evidence for an association between specialization in baseball and overuse injury is mixed [17]. Our results indicate that many parents may not be aware of the research linking specialization with an increased risk of injury, or perhaps more likely, view the potential benefits of specialization as outweighing the potential injury consequences.…”
Section: Discussionsupporting
confidence: 91%
“…5,9 The impetus for this shift toward specialization is likely multifactorial, perhaps stemming from the desire for a competitive advantage, the possibility for scholarships, the positive public perception of elite athletes, or pressure from coaches 33,43 or parents. [6][7][8]32 The concern with this trend of early sport specialization (ESS) and an increased early high training volume (HTV) in youth athletes is that there may be a potential for an increased risk of overuse/overload injuries 12,13,16 as well as acute injuries requiring surgery. ESS and the injuries that can accompany it may also lead to burnout, fear of reinjuries, difficulty returning to preinjury skill levels, and early sport retirement.…”
mentioning
confidence: 99%
“…13 The relative risk of injury was significantly higher in ultracompetitive regions known to produce high-level collegiate prospects. 18,19 As health care providers become increasingly aware of the epidemic of elbow injuries in young baseball players, accurate distribution of preventative information to the baseball community is necessary. This begins with expanding the role of clinicians from a focus on treatment to a focus on preventative education.…”
mentioning
confidence: 99%